2017
DOI: 10.1111/1440-1681.12734
|View full text |Cite
|
Sign up to set email alerts
|

The intrauterine renin–angiotensin system: Sex‐specific effects on the prevalence of spontaneous preterm birth

Abstract: Preterm birth (PTB) is the single largest cause of death in infants and young children. The rate of PTB is significantly higher in male infants, particularly those that are born very preterm. Here we present evidence to suggest that the decidual renin-angiotensin system may play a role in inhibiting inflammation and maintaining the integrity of the fetal membranes during pregnancy, and that sex-specific alterations in the intrauterine RAS could contribute to the increased risk of PTB in male babies. Women carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The detection of a co-expression of Ang(1− 7) and TDO in healthy placentas, which we found to be more represented in the villi and fetal side of the placenta compared to the maternal side, is a novel finding, and suggests the existence of an interaction between the KP and RAS in pregnancy. All components of the intrauterine RAS have been identified in term human decidua, myometrium, and fetal membranes (Pringle et al, 2017(Pringle et al, , 2011 and they are involved in placental development through processes such as angiogenesis, modulation of placental blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of a co-expression of Ang(1− 7) and TDO in healthy placentas, which we found to be more represented in the villi and fetal side of the placenta compared to the maternal side, is a novel finding, and suggests the existence of an interaction between the KP and RAS in pregnancy. All components of the intrauterine RAS have been identified in term human decidua, myometrium, and fetal membranes (Pringle et al, 2017(Pringle et al, , 2011 and they are involved in placental development through processes such as angiogenesis, modulation of placental blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II stimulates the secretion of aldosterone, which regulates uteroplacental vasoconstriction and blood pressure [9]. Previous studies have shown that an increase in uteroplacental blood pressure is associated with the development of PTB, preeclampsia, and spontaneous abortion [10,11,12].…”
Section: Introductionmentioning
confidence: 99%